Preparation method and application of iron-platinum diatomic catalyst
By using the preparation method of iron-platinum diatom catalyst in fuel cells, the strong binding of iron atoms and the synergistic effect of platinum atoms and platinum atoms is used to solve the problems of high cost of precious metal platinum-based catalysts and poor stability of non-precious metal iron-based materials. A catalyst with high activity and high stability is achieved, and the performance of fuel cells is improved.
Patent Information
- Application Number
- CN202411092670.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, when noble metal platinum-based catalysts are used in fuel cells, due to high costs and scarce resources, they have problems with low platinum atom utilization rate in large-scale applications, and the stability of non-precious metal-based materials such as iron-based atomic materials. Poor performance and cannot effectively improve the performance of fuel cells.
Using a preparation method, zinc nitrate hexahydrate and iron acetate are dissolved and mixed with 2-methylimidazole, and heat reduction is used to form iron-nitrogen-carbon material, and then ultrasonic treatment is carried out with metal chelating agent and platinum precursor to obtain iron Platinum diatom catalyst, through this method, iron atoms bind to the carbon support more firmly, avoiding the formation of FePt alloys, and improving the stability and activity of the catalyst.
The prepared iron-platinum diatom catalyst exhibits excellent activity and stability in oxygen reduction reaction, which reduces the activation polarization loss of the fuel cell, improves the performance of the fuel cell, and improves the synergistic effect of the carbon support and platinum atoms. The platinum atom utilization rate of the catalyst.
Smart Images

Figure CN119230848A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a preparation method and application of an iron-platinum diatomic catalyst. Background Art
[0002] With the consumption of fossil fuels, energy shortages and serious pollution have become major issues related to the sustainable development of human society. Therefore, the development of renewable clean energy has inevitably become a research hotspot. Among the promising high-efficiency electrochemical energy conversion devices, proton exchange membrane fuel cells (PEMFCs) are considered to be the most ideal next-generation energy conversion devices due to their near-zero emissions, wide range of applications and high energy density. The energy conversion process of PEMFCs is mainly determined by the slow oxygen reduction reaction (ORR) kinetics because of the multi-step proton-coupled electron transfer involved. During the oxygen reduction process, oxygen molecules are converted to H2O2 through a two-electron pathway, or reduced to OH- or H2O through a four-electron pathway in an alkaline or acidic environment, respectively. Pt-based materials are considered to be ideal catalysts for promoting the ORR process due to their good catalytic performance, but their high cost and scarcity of resources have severely limited their large-scale application. Therefore, one of the important ways to improve the performance of PEMFCs is to develop catalysts with high platinum atomic utilization. Summary of the invention
[0003] The purpose of the present invention is to provide an iron-platinum diatomic catalyst with high activity and high stability, which can be applied to the cathode catalyst layer of a fuel cell, thereby reducing the activation polarization loss of the fuel cell and improving the performance of the fuel cell.
[0004] In order to achieve the above object, the present invention provides a method for preparing an iron-platinum diatomic catalyst, which comprises at least the following steps:
[0005] Step 1, dissolving zinc nitrate hexahydrate and ferric acetate in N,N-dimethylformamide to obtain a first solution, and dissolving 2-methylimidazole in N,N-dimethylformamide to obtain a second solution;
[0006] Step 2, mixing the first solution and the second solution to obtain a third solution, keeping the third solution at a constant temperature of 100° C. to 160° C. and then centrifuging and washing to obtain a precipitate, and vacuum drying the precipitate at 30° C. to 60° C. to obtain a first precursor;
[0007] Step 3, placing the first precursor in a tube furnace for thermal reduction under an atmosphere of a first protective gas to obtain an iron-nitrogen-carbon material;
[0008] Step 4, dispersing the iron-nitrogen-carbon material in a solution, adding a metal chelating agent and a second precursor to the solution, removing the solvent after ultrasonic treatment, and thermally reducing the solution in a tubular furnace under an atmosphere of a second protective gas to obtain an iron-platinum diatomic catalyst.
[0009] Preferably, in step 1, in terms of mass ratio, the zinc nitrate hexahydrate: ferric acetate = 8:1 to 2:1; the 2-methylimidazole: zinc nitrate hexahydrate = 8:1 to 1:1.
[0010] Preferably, in step 1, the concentration of zinc nitrate hexahydrate in the first solution is 0.01M to 0.1M, and the concentration of 2-methylimidazole in the second solution is 0.01M to 0.2M.
[0011] Preferably, in step 3, the first protective gas is selected from nitrogen and / or argon; in step 4, the second protective gas is selected from any one of hydrogen, nitrogen, argon, methane, acetylene, ethane, propane, ammonia, carbon monoxide, or a combination of any two or more thereof.
[0012] Preferably, in step 3, the temperature of the thermal reduction is 900°C to 1300°C, and the time of the thermal reduction is 0.5h to 8h; in step 4, the temperature of the thermal reduction is 200°C to 400°C, and the time of the thermal reduction is 0.1h to 1h.
[0013] Preferably, in step 4, the metal chelating agent is selected from any one of 1,10-phenanthroline, sodium citrate, and ethylenediaminetetraacetic acid, or a combination of any two or more thereof.
[0014] Preferably, in step 4, the second precursor is selected from any one of H2PtCl6, K2PtCl4, ammonium chloroplatinate, and platinum acetylacetonate, or a combination of any two or more thereof.
[0015] Preferably, in step 4, the method for removing the solvent comprises at least one of freeze-drying, natural air drying, drying, water bath evaporation and oil bath evaporation.
[0016] Preferably, the content of the metal component in the iron-platinum diatomic catalyst is in the range of 6% to 60%.
[0017] The present invention also provides an application of an iron-platinum diatomic catalyst, wherein the iron-platinum diatomic catalyst is used to prepare a cathode catalyst layer of a fuel cell membrane electrode.
[0018] Compared with the prior art, the beneficial effects of the present invention include at least:
[0019] (1) The present invention first dissolves zinc nitrate hexahydrate and ferric acetate in N,N-dimethylformamide to obtain a first solution, dissolves 2-methylimidazole in N,N-dimethylformamide to obtain a second solution, mixes the first solution and the second solution, and then obtains an iron-nitrogen-carbon material through centrifugal drying and thermal reduction. The iron atoms and the carbon carrier are formed together, which is equivalent to the iron atoms being embedded in the carbon carrier, thereby avoiding the formation of FePt alloys with the platinum atoms, so that the iron atoms on the iron-platinum diatomic catalyst prepared by the present invention have a stronger binding force with the carbon carrier, and the synthesized iron-platinum diatomic catalyst has a higher stability.
[0020] (2) Compared with commercial Pt / C, the activity of the iron-platinum diatomic catalyst is higher because the carbon carrier will affect the electronic structure of the active site Pt, thereby affecting the catalytic activity of the catalyst. Therefore, there is a synergistic effect between the carbon carrier and the platinum atom in the iron-platinum diatomic catalyst of the present invention, making the synthesized iron-platinum diatomic catalyst more active. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The morphology and element distribution diagram of the iron-platinum diatomic catalyst in Example 1 of the present invention;
[0022] Figure 1 a is the morphology of the iron-platinum diatomic catalyst in Example 1;
[0023] Figure 1 b is the element distribution diagram of Pt in the iron-platinum diatomic catalyst in Example 1;
[0024] Figure 1 c is the element distribution diagram of Fe in the iron-platinum diatomic catalyst in Example 1.
[0025] Figure 2 XRD diffraction patterns of the iron-platinum diatomic catalyst Fe-Pt@NC of Example 1 and LT-Fe-Pt@NC of Example 4 at different thermal reduction temperatures of the present invention.
[0026] Figure 3 This is a performance test diagram of the Fe-Pt@NC series iron-platinum diatomic catalyst applied to electrocatalytic oxygen reduction under three electrodes in Example 5 of the present invention.
[0027] Figure 4 This is a performance test diagram of the Fe-Pt@NC series iron-platinum diatomic catalyst applied to the cathode of a low-temperature proton exchange membrane fuel cell in Example 6 of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0029] The use of non-precious metal-based materials instead of traditional platinum group catalysts to catalyze the oxygen reduction reaction (ORR) on the cathode side of the PEMFC membrane electrode is often strongly limited by its actual performance. Among them, iron-based atomic materials are considered to be very promising candidate materials. Compared with other non-precious metal-based materials, they have higher initial activity, but their stability is poor and cannot be used in actual PEMFCs. Chen et al. synthesized a new MX4 catalyst composed of Fe-N4 centers and non-coordinated B heteroatoms (FeNC+B) by adjusting the content of boric acid (Adv. Funct. Mater. 2021, 31, 2011289.), which has a high initial activity, but as the reaction proceeds, Fe atoms begin to fall off the carbon support, N groups are protonated, and carbon corrosion intensifies, resulting in poor stability of the catalyst. Zhou et al. used the strong metal-support interaction effect to synthesize a highly dispersed CoNi bimetallic catalyst on the surface of a carbon support and observed for the first time the interaction between almost atomically dispersed cobalt and nickel atoms, but could not clearly identify the diatomic clusters and reaction mechanisms of the metal atomic spacing (Appl. Catal., B 2021, 280, 119448.). There are studies on the preparation method and application of a Fe and Pt diatomic catalyst, but the iron atoms are loaded on commercial carbon black by the impregnation reduction method, which will cause the carbon support and iron atoms to be not firmly bonded, and will cause the iron atoms to fall off during the actual use of the catalyst, resulting in the degradation of the catalyst performance; there are also studies on a diatomic iron catalyst and its preparation method and application, but it uses a dioxygen-bridged iron Schiff base complex in the synthesis process, which is expensive and difficult to obtain, resulting in its cost being much higher than that of platinum-based catalysts and cannot be mass-produced.
[0030] Based on the problems of the above-mentioned iron-based atomic materials, the present invention proposes a new method for preparing an iron-platinum-based diatomic catalyst. Due to the effect of atomic-level dispersion, the catalyst can not only significantly reduce the platinum loading on the membrane electrode, but also adjacent iron-platinum atomic pairs show a synergistic effect and exhibit a higher protonation free energy, making the synthesized catalyst highly stable. The iron-platinum diatomic catalyst prepared by this method exhibits excellent activity and stability for oxygen reduction reaction (ORR).
[0031] Example 1
[0032] 1.2 g of zinc nitrate hexahydrate and 0.3 g of ferric acetate were dissolved in 100 mL of N,N-dimethylformamide by magnetic stirring, which was recorded as the first solution; 0.65 g of 2-methylimidazole was dissolved in 100 mL of N,N-dimethylformamide by magnetic stirring, which was recorded as the second solution. The first solution and the second solution were mixed evenly to form a third solution. The third solution was kept at 140°C for 24 hours, centrifuged and washed, and vacuum dried at 50°C to obtain the first precursor. The first precursor was thermally reduced in a tube furnace under a nitrogen atmosphere, the thermal reduction temperature was 1100°C, and the thermal reduction time was 2 hours to obtain an iron-nitrogen-carbon material. The obtained iron-nitrogen-carbon material was dispersed in 100 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 1:1), 0.2 g of 1,10-phenanthroline and 0.12 g of H2PtCl6 were added, and the solvent was removed by freeze-drying after ultrasonic treatment for 120 minutes. The material was thermally reduced at 200°C in a tubular furnace under 5% hydrogen-argon mixed gas for 0.5 hour, and the iron-platinum diatomic catalyst Fe-Pt@NC was obtained after the furnace was cooled.
[0033] The iron-platinum diatomic catalyst Fe-Pt@NC prepared in Example 1 was observed by scanning electron microscopy. Figure 1 shown.
[0034] Example 2
[0035] In Example 2, the amount of H2PtCl6 added was changed to 0.24 g, and the other reaction conditions were the same as those in Example 1, to prepare an iron-platinum diatomic catalyst Fe-Pt2@NC.
[0036] Example 3
[0037] In Example 3, the amount of ferric acetate added was changed to 0.6 g, and the other reaction conditions were the same as those in Example 1, to prepare an iron-platinum diatomic catalyst Fe2-Pt@NC.
[0038] Example 4
[0039] The iron-platinum diatomic catalyst LT-Fe-Pt@NC was prepared by changing the phrase "thermal reduction at 200°C in a tubular furnace for 0.5 hour under a 5% hydrogen-argon mixture" in Example 1 to "thermal reduction at 150°C in a tubular furnace for 0.5 hour under a 5% hydrogen-argon mixture".
[0040] XRD scanning was performed on the iron-platinum diatomic catalyst Fe-Pt@NC and the iron-platinum diatomic catalyst LT-Fe-Pt@NC prepared in Example 1 and Example 4, and the results are as follows: Figure 2 As shown, the peak value of the iron-platinum diatomic catalyst Fe-Pt@NC prepared in Example 1 is higher.
[0041] Example 5
[0042] The electrochemical test under the three-electrode system is used to characterize the oxygen reduction activity of the catalyst. The electrolyte solution of this system is 0.1M HClO4, the counter electrode is a Pt sheet electrode, and the reference electrode is a saturated Ag / AgCl electrode. The electrolyte solution of the cyclic voltammetry test is saturated with N2, and the test system is Gamry 3000; the ORR test solution is saturated with O2. Preparation of the rotating disk electrode membrane catalyst layer: 2mg catalyst, 1mL ethanol, ultrasound; add 10μL of 5wt% Nafion solution, ultrasound, and take 8μL of the above dispersed slurry to coat the surface of the rotating disk electrode as the working electrode. The experimental results are as follows Figure 3 As shown, it is shown that the iron-platinum diatomic catalyst Fe-Pt@NC prepared in Example 1 has the strongest performance.
[0043] Example 6
[0044] The performance of a 2cm*2cm single cell was tested under hydrogen and oxygen conditions to characterize the catalytic activity of the iron-platinum diatomic catalyst in the actual working environment of the fuel cell cathode. The anode is a 20% Pt / C catalyst, and the cathode is a slurry of iron-platinum diatomic catalyst ultrasonic spraying. The platinum loadings of the anode and cathode are 0.1 and 0.2 mgPt / cm respectively. 2 The battery temperature is 60°C, and the back pressure on the anode and cathode sides is 100 kPa. The experimental results are as follows: Figure 4 As shown, the peak power density of the samples of Examples 1-4 is 958, 988, 1010, and 1066 mW / cm 2 Experiments show that the Fe-Pt@NC iron-platinum diatomic catalyst series has good application prospects in low-temperature proton exchange membrane fuel cells.
[0045] In summary, the present invention prepares an iron-platinum diatomic catalyst, which has excellent electrocatalytic oxygen reduction activity and stability, and has important value and application in proton exchange membrane fuel cells and oxygen reduction catalysis. The iron-platinum diatomic catalyst LT-Fe-Pt@NC prepared by the present invention exhibits high activity (0.47Amg at 0.9 V (vs RHE) Pt -1 ), is a commercial Pt / C (0.11 Amg Pt -1 ) is 4.2 times of that of LT-Fe-Pt@NC. When LT-Fe-Pt@NC is used as cathode catalyst for low-temperature proton exchange membrane fuel cells (Pt loading is 0.2 mg Pt cm -2 ) Its peak power is 1.066 W cm -2 The present invention provides a new idea for the synthesis of diatomic catalysts, and promotes the development of iron-platinum diatomic catalysts in the application of low-temperature proton exchange membrane fuel cells.
[0046] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing an iron-platinum diatomic catalyst, characterized in that: At least the following steps are included: Step 1, dissolving zinc nitrate hexahydrate and ferric acetate in N,N-dimethylformamide to obtain a first solution, and dissolving 2-methylimidazole in N,N-dimethylformamide to obtain a second solution; Step 2, mixing the first solution and the second solution to obtain a third solution, keeping the third solution at a constant temperature of 100° C. to 160° C. and then centrifuging and washing to obtain a precipitate, and vacuum drying the precipitate at 30° C. to 60° C. to obtain a first precursor; Step 3, placing the first precursor in a tube furnace for thermal reduction under an atmosphere of a first protective gas to obtain an iron-nitrogen-carbon material; Step 4, dispersing the iron-nitrogen-carbon material in a solution, adding a metal chelating agent and a second precursor to the solution, removing the solvent after ultrasonic treatment, and thermally reducing the solution in a tubular furnace under an atmosphere of a second protective gas to obtain an iron-platinum diatomic catalyst.
2. The preparation method according to claim 1, characterized in that In step 1, in terms of mass ratio, the zinc nitrate hexahydrate: ferric acetate = 8:1 to 2:1; the 2-methylimidazole: zinc nitrate hexahydrate = 8:1 to 1:
1.
3. The preparation method according to claim 1, characterized in that: In step 1, the concentration of zinc nitrate hexahydrate in the first solution is 0.01M to 0.1M, and the concentration of 2-methylimidazole in the second solution is 0.01M to 0.2M.
4. The preparation method according to claim 1, characterized in that: In step 3, the first protective gas is selected from nitrogen and / or argon; in step 4, the second protective gas is selected from any one of hydrogen, nitrogen, argon, methane, acetylene, ethane, propane, ammonia, carbon monoxide, or a combination of any two or more thereof.
5. The preparation method according to claim 1, characterized in that: In step 3, the temperature of the thermal reduction is 900°C to 1300°C, and the time of the thermal reduction is 0.5h to 8h; in step 4, the temperature of the thermal reduction is 200°C to 400°C, and the time of the thermal reduction is 0.1h to 1h.
6. The preparation method according to claim 1, characterized in that: In step 4, the metal chelating agent is selected from any one of 1,10-phenanthroline, sodium citrate, and ethylenediaminetetraacetic acid, or a combination of any two or more thereof.
7. The preparation method according to claim 1, characterized in that: In step 4, the second precursor is selected from any one of H2PtCl6, K2PtCl4, ammonium chloroplatinate, and platinum acetylacetonate, or a combination of any two or more thereof.
8. The preparation method according to claim 1, characterized in that: In step 4, the method for removing the solvent includes at least one of freeze-drying, natural air drying, drying, water bath evaporation, and oil bath evaporation.
9. The preparation method according to claim 1, characterized in that: The content of the metal component in the iron-platinum diatomic catalyst is in the range of 6% to 60%.
10. Use of the iron-platinum diatomic catalyst according to any one of claims 1 to 9, characterized in that: The iron-platinum diatomic catalyst is used for preparing the cathode catalyst layer of the fuel cell membrane electrode.
